Current recombinant vaccine strategy as a novel approach to prevent Ebola virus diseases: a literature review - Agus Simahendra; Ni Luh Putu Harta Wedari; I Wayan Adi Pranata; Ni Nyoman Sri Budayanti (Journal of Clinical Microbiology and Infectious Diseases, 2021)
Ebola virus has resulted in a devastating hemorrhagic fever epidemic spanning several African countries and leading to thousands of deaths. There have been no vaccines approved or medication strategies toward successful prophylaxis and therapeutics critical until the rVSV-ZEBOV vaccine approved by the US Food and Drug Administration (FDA) in December 2019 as a preventative measure for people aged 18 years old and/or older. Several experimental vaccines are showing some promise. The most advanced vaccine is the clinically tested recombinant vesicular-stomatitis virus (rVSV) which encodes EBOV glycoprotein, widely known as the V920 vaccine candidate. This vaccine induces antibody-producing responses in non-human primate models, and current clinical trials suggest protective efficacy in humans. Although generally well-tolerated, the administration of this vaccine was complicated by occurrences of side effects. The development of vaccine platforms is also challenging, given that Ebola virus diseases have now reached epidemic proportions in some localities. Outcomes in terms of viral persistence after recovery are unknown, and a study explaining the role of adaptive immunity in recovery may be essential to inform effective vaccine design. This review aims to give a basic understanding on the general immunity mechanism elicited by recombinant vector vaccines and the current implementation of this relatively new technology to tackle a major infectious disease outbreak.